2014
DOI: 10.1186/s13054-014-0500-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimated cerebral oxyhemoglobin as a useful indicator of neuroprotection in patients with post-cardiac arrest syndrome: a prospective, multicenter observational study

Abstract: IntroductionLittle is known about oxyhemoglobin (oxy-Hb) levels in the cerebral tissue during the development of anoxic and ischemic brain injury. We hypothesized that the estimated cerebral oxy-Hb level, a product of Hb and regional cerebral oxygen saturation (rSO2), determined at hospital arrival may reflect the level of neuroprotection in patients with post-cardiac arrest syndrome (PCAS).MethodsThe Japan Prediction of neurological Outcomes in patients with Post cardiac arrest (J-POP) registry is a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…The main strength of this study is that rSo 2 data were collected throughout CPR for the purpose of studying the association between cerebral oxygenation with ROSC (11-16) and survival with favorable neurologic outcomes (17,18). The clinical utility of this study lies in identifying a real-time, noninvasive method to quantify cerebral oxygen delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main strength of this study is that rSo 2 data were collected throughout CPR for the purpose of studying the association between cerebral oxygenation with ROSC (11-16) and survival with favorable neurologic outcomes (17,18). The clinical utility of this study lies in identifying a real-time, noninvasive method to quantify cerebral oxygen delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of small studies have indicated that ROSC is associated with higher rSo 2 during CPR in out-of-hospital CA (OHCA) and in-hospital CA (IHCA) (11)(12)(13)(14)(15)(16), they lacked the power to determine the accuracy and clinical utility of rSo 2 as a predictor of ROSC. Recently, a single rSo 2 measured on arrival to the emergency department was found to predict survival with favorable neurologic outcomes at 90 days after OHCA (17,18). However, a single rSo 2 is unlikely to reflect the overall balance between cerebral ischemia and oxygen delivery throughout CPR.…”
mentioning
confidence: 98%
“…It is increasingly evident that secondary injury leads to adverse neurologic outcome and identification of ongoing brain hypoxia after ROSC is imperative. Human studies have principally focussed on establishing links between decreased rSO2 as a surrogate marker of brain oxygenation and neurological outcome, but have yielded conflicting results in its predictive utility (30)(31)(32)(33). These conflicting results, along with technical limitations of NIRS have hindered its routine use in evaluating brain hypoxia post cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…11,14,15 The SOS-KANTO study group reported favorable short-term neurological outcome in patients with higher post arrest hemoglobin level. Study patients in the good neurological outcome group had a median hemoglobin level of 14.4 g/dl vs. 12.8 g/dl in the bad outcome group.…”
Section: Discussionmentioning
confidence: 99%